Transcription facilitates sister chromatid cohesion on chromosomal arms. - Bhardwaj, S; Schlackow, M; Rabajdova, M; Gullerova, M (Oxford University Press, 2016)
Cohesin is a multi-subunit protein complex essential for sister chromatid cohesion, gene expression and DNA damage repair. Although structurally well studied, the underlying determinant of cohesion establishment on chromosomal arms remains enigmatic. Here, we show two populations of functionally distinct cohesin on chromosomal arms using a combination of genomics and single-locus specific DNA-FISH analysis. Chromatin bound cohesin at the loading sites co-localizes with Pds5 and Eso1 resulting in stable cohesion. In contrast, cohesin independent of its loader is unable to maintain cohesion and associates with chromatin in a dynamic manner. Cohesive sites coincide with highly expressed genes and transcription inhibition leads to destabilization of cohesin on chromatin. Furthermore, induction of transcription results inde novorecruitment of cohesive cohesin. Our data suggest that transcription facilitates cohesin loading onto chromosomal arms and is a key determinant of cohesive sites in fission yeast.